(untitled) (Journal of Parents and Teachers, 1996)
The article reflects on the beginning of the school year and the arrival of autumn, highlighting the importance of education and the impact on students. The need for a humanistic and creative approach to teaching is emphasized. In addition, the nostalgia and memories associated with the change of seasons are evoked.